The role of germination microsite in the establishment of sugar pine and Jeffrey pine seedlings - Legras, Elaine C.; Vander Wall, Stephen B.; Board, David I. (Forest ecology and management, 2010)
Mature shrubs can provide microhabitats that are beneficial to tree seedling growth and development. Sugar pine trees ( Pinus lambertiana) grow in a narrow zone on the eastern slope of the Carson Range in extreme western Nevada, whereas Jeffrey pine ( Pinus jeffreyi) is the dominant tree species in the region, an area extensively disturbed by wild fire. This study compares seedling establishment of sugar pine and Jeffrey pine relative to mature shrubs. In the fall of 2002 (cohort 1) and 2003 (cohort 2), 13,600 seeds of both species were planted in wire mesh enclosures, at three sites, under a variety of microhabitat treatments: under shade and in the open, under two species of shrub cover, and with and without plant litter. Seedlings were monitored for survival through two growing seasons. Even though more sugar pine seedlings emerged, more Jeffrey pine seedlings survived, and Jeffrey pine was the more drought tolerant species, better suited for the xeric climate found in the Carson Range. Litter slightly hindered seedling emergence but had no effect on survival and there was no significant species × litter interaction. Supplemental water facilitated survival in all treatments with highest survival in shade treatments. Sugar pine seedlings showed a significant increase in survival over Jeffrey pine seedlings with the addition of water, particularly in open treatments and more of both species survived under manzanita shrubs with water. The highest seedling mortality occurred when shrub canopy was removed, and seedlings experienced the effect of full sun and competition for soil water. For either species, microhabitat is a significant factor in determining success or failure in rehabilitation efforts after disturbance.